Social and political neologism as a means of enriching the modern Russian language (2016-2020) - Хизанцян, Анна (Bulletin of Yerevan University H: Russian Philology, 2021)
This article analyzes the socio-political neologisms that appeared in the Russian language for the period 2016-2020. The research was carried out on the basis of the materials of the sociolinguistic project entitled "Dictionary of Change". During the study, scientific points of view on the object of a new direction in linguistics – neology, and on the criteria that define the lexeme as a neologism were considered. The analyzed lexical material was classified according to two principles – the reasons (extra-linguistic factors) of the emergence of neologisms in the language and the word-formation models. An attempt was also made to identify the most common lexical-thematic groups and to determine their superordinate.